12 A single centre experience of STEMI in the elderly population (>80 years). (October 2018) - Yearoo, I; Teehan, S; Hennessey, B; Fitzpatrick, N; Brennan, A; Brandon, L; Alshammari, B Kerr M; Srinivas, P; Daly, C; Crean, P; Cosgrave, J; Murphy, R
Abstract : Introduction: The elderly population (aged 80 years or older) with acute coronary syndrome is a heterogeneous group with variable frailty and differences in physiological ageing, comorbidity and functional status. Treatment of elderly patients is challenging because they are more likely than younger patients to have atypical symptoms. Methods: We undertook a review of the elderly population that were diagnosed as an inpatient with a ST elevation MI (STEMI). We collected data from October 2016 to October 2017. We examined how many over 80's patients had invasive angiography and looked at key performance indicators such as ECG to door time (DDT) and ECG to reperfusion time (RT) and the inpatient mortality rate. Our aim was to see if these patients are less likely to receive invasive treatment within the ESC recommendations and if they are at a higher risk for adverse events. Results: In the 1 year review of our database, there were 480 patients referred as a code STEMI to our cardiology service or diagnosed as an inpatient. The average age was 61.2 years (median 60, range 18–94 years), 18% (88) female. This included 34 patients aged 80 years and older, average age 85 (range 80–94). 19 (56%) were male with an average age of 84.6 years (median 84, range 80–93). The average female age was 85.6 years (median 85, range 80–94). The average DDT was 100 min (range 25–455, 47% were over 90 min). In our Emergency Department, the average door to ECG time was 10 min (range 8–13). Baseline comorbidities in this cohort included diabetes 22%, Current or ex-smokers were 36%, dyslipidaemia 38% and known hypertension in 38%. STEMI was the confirmed diagnosis in all 34 patients who underwent invasive coronary angiography and the preferred route was the right radial artery in 91% of cases (31 patients). The average Reperfusion time (RT) was 133 min (range 45–335, 60% over 120 min). Nine patients did not survive to discharge, a mortality rate 26% versus 3% in the under 80's. Four patients (12%) arrested and died during primary PCI having been in cardiogenic shock on arrival to the Cath lab. These patients were evaluated with a mean follow-up of 11 months (range 5–15 months) and we report an all cause 26% all-cause mortality rate. We used hospital and general practice records and the national mortality data. Conclusion: Time-to-admission and reperfusion time for ST-segment elevation myocardial infarction in the elderly (>80 years) are still prolonged. Resources should be directed to early recognition of the acute myocardial infarction, improved utilization of emergency services for transportation, and prehospital diagnosis and triaging. Ambulances equipped with wireless capability to transmit electrocardiograms to the on-call cardiologist have achieved earlier diagnosis and triaging with high diagnostic sensitivity and specificity. It is important to identify STEMI in this high-risk group early to achieve higher rates of reperfusion times within 120 min.